Analisis lingkungan eksternal dan internal dalam sebuah organisasi - syahlatunnisa, syifa (Maliki Interdisciplinary Journal, 2025)
This study aims to examine the critical role of environmental analysis in supporting effective strategic decision-making. Internal environmental analysis focuses on assessing resources, organizational structure, work culture, and managerial capabilities that influence organizational performance and competitiveness. Meanwhile, external environmental analysis encompasses factors beyond the organization's control, such as economic conditions, government policies, technological developments, and the level of market competition.Through the application of SWOT analysis, organizations can identify strengths, weaknesses, opportunities, and threats as a basis for formulating more adaptive and targeted strategies. The study's results indicate that integrating internal and external environmental analysis can help organizations adapt their strategies to changes in the business environment, improve planning effectiveness, and strengthen their competitive position in the market.